Emotional impact of crowding and coping behavior of visitors at Kukup Island National Park, Johor, Malaysia - Rosli, Noor Haslidawati (2016)
Recently, the number of visitors to natural places like National Park is steadily increasing. The Kukup Island National Park is one of the most visited National Parks in Malaysia, with more than 10,000 visitors visiting the Kukup Island National Park each year. The purpose of this study was to determine the visitors’ perception of the crowding situation in the Kukup Island National Park that impacts their emotional responses and coping behaviors. Hence, this research also wants to determine the relationship between emotional response and coping behavior. A survey was administered to a sample of visitors that using the facilities in the Kukup Island National Park. A total of 380 respondents that visit the Kukup Island National Park as samples in the study. A descriptive analysis was employed in this study to determine the perception of visitors on crowding condition in the Kukup Island National Park. There are nine facilities that were used by visitors during their visit to the park. Visitors felt “moderately crowded” during using facilities in the park area. It is based on a 9 point Likert Scale which is from scale 5 to 7. Besides that, this study was to examine the impact of crowding on visitors’emotional response. Through ANOVA analysis, the findings show that crowding gives impacts to the pleasure and arousal emotions. The findings suggest that visitors who felt crowded were less likely to feel pleasured and were not aroused of their recreational activities. Then, visitors felt unhappy, not joy but just content during a lot of visitors in the park. While a concept of dominance does not significantly impact when there were a lot of visitors in the park. The emotional response showed a strong relationship with the behavioral coping mechanism. Sixty-eight percent of the variance in the measurement of coping behavior explains by emotional responses. It can be concluded that visitors’emotions were affected; they have more tendencies to practice the behavioral coping mechanism. The finding from this study provides baseline information to park managers or recreational sites on the appropriate course of actions to be taken in order to solve crowding problem in their respective parks or recreational areas. Other than that, this study also provides visitors with the information on how to cope with a crowded condition, especially in the National Park or state park.